Reduced cell viability and apoptosis induction in human thyroid carcinoma and mesothelioma cells exposed to cidofovir. (June 2017) - Catalani, Simona; Palma, Francesco; Battistelli, Serafina; Nuvoli, Barbara; Galati, Rossella; Benedetti, Serena
Abstract: Besides its well-recognized antiviral activity, Cidofovir (CDV) has been shown to exert anticancer properties both within in vitro and in vivo models. The aim of this study was to evaluate the effects of CDV on still unexplored cultured cancer cells from human mesothelioma as well as breast, colon, liver, lung, prostate, and thyroid carcinomas. Overall, a dose- and time-dependent inhibition of cell viability was observed after CDV exposure. To clarify the mechanisms underlying CDV action, apoptotic cell death was investigated in two infected cell lines [Ist-Mes1 and Ist-Mes2 mesothelioma cells (SV40 +)] and in two uninfected cell lines (NCI-H2425 mesothelioma cells and FTC-133 thyroid cancer cells), which resulted the most sensitive to CDV treatment. Reduced expression of procaspase-3 and increased expression of PARP p85 fragment were observed in both infected and uninfected mesothelioma cells, indicating apoptosis induction by CDV in a virus-independent manner. Similarly, the increase of the pro-apoptotic proteins p53, cytochrome c and caspase-3, the decrease of the survival protein Bcl-x, and the increment of Bax/Bcl-2 ratio revealed the occurrence of apoptosis in CDV-treated FTC-133. The presence of nuclear DNA fragmentation confirmed apoptotic cell death by CDV. Overall, our findings warrant further investigations to explore the therapeutic potential of CDV for human mesothelioma and follicular thyroid carcinoma. Highlights: CDV showed antitumor activity against virus-infected and -uninfected cancer cells. CDV induced intrinsic apoptosis in human thyroid carcinoma and mesothelioma cells. Thyroid carcinoma and mesothelioma could benefit from CDV treatment.